2015
DOI: 10.1016/j.jacr.2014.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computerized Physician Order Entry on Imaging Study Indication

Abstract: The effect of computerized physician order entry (CPOE) on imaging indication quality had only been measured in one institution’s emergency department using a homegrown electronic health record with faculty physicians, and only with one instrument. To better understand how many US hospitals’ recent CPOE implementations had affected indication quality, we measured its effect in a generalizable inpatient setting, using one existing and one novel instrument. We retrospectively analyzed the indications for 100 ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…This is supported by Pevnick et al who reported the improved data exchange between the radiology information system and the CPOE system studied (28). According to findings of the current study and studies noted above, paying attention to the decision support aspect of the CPOE systems, when designing or improving the systems, can help to minimize medication errors and improve patient safety.…”
Section: Discussionsupporting
confidence: 53%
“…This is supported by Pevnick et al who reported the improved data exchange between the radiology information system and the CPOE system studied (28). According to findings of the current study and studies noted above, paying attention to the decision support aspect of the CPOE systems, when designing or improving the systems, can help to minimize medication errors and improve patient safety.…”
Section: Discussionsupporting
confidence: 53%
“…The use of CPOE has been reported to enhance communication of such information in imaging requests [19], and although additional unstructured free text clinical data were available in our initial implementation of CDS, it was not usable by the software in over 75% of all requests [6]. After review of the unstructured free text data accompanying requests, the percentage of requests with insufficient information to determine the AR fell to 6.4%.…”
Section: Discussionmentioning
confidence: 93%
“…It is not expected that clinicians will provide an exhaustive history, but rather, key points which may help radiologists choose imaging as effectively as possible. With increasing access to electronic medical records, radiologists may have increasing access to patient history, however, the acute clinical interaction at the time of the ED visit may still provide additional information required by the radiologist [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This subjectivity is a limitation of our current study. However, at present, there are no available gold standards for determining history quality and different authors have used different techniques and statistical analyses to evaluate quality of history in a few previously published manuscripts [ 11 , 12 ]. As the imaging requisition is a medical document included in the patient encounter, the grading system utilized in this study was based on criteria described in guidelines for documentation of patient encounters and subsequent papers regarding the guidelines’ clinical application [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation